Possibilities for cooperation between the non-governmental, non-commercial sector and the public sector in modern Russia - Jach, Anna (Eastern Review, 2020)
The model of three-sector synergy in a contemporary state rests on cooperation between the first (state) sector, the second (commercial) sector, and the third sector – the civil one, also referred to as the non-commercial sector. The quest for an optimal solution and the establishment of mutual relations is underpinned by the concept of the reorganization of Russian society with regard to its political modernization; this is accompanied by a variant of social agreement that guarantees citizens equality before the law, and the protection of their rights along with simultaneous compliance with the law. What complements the image of Russia’s contemporary reality is the goal of non-governmental, non-commercial organizations – not only to survive but also to develop a modus vivendi in the circumstances of an authoritarian state.